Short-term water stress responses of grafted pepper plants are associated with changes in the hormonal balance - Padilla, Yaiza Gara; Gisbert-Mullor, Ramón; López-Galarza, Salvador; Albacete, Alfonso; Martínez-Melgarejo, Purificación A.; Calatayud, Ángeles (Frontiers in Plant Science, 2023)
Phytohormones play an important role in regulating the plant behavior to drought. In previous studies, NIBER® pepper rootstock showed tolerance to drought in terms of production and fruit quality compared to ungrafted plants. In this study, our hypothesis was that short-term exposure to water stress in young, grafted pepper plants would shed light on tolerance to drought in terms of modulation of the hormonal balance. To validate this hypothesis, fresh weight, water use efficiency (WUE) and the main hormone classes were analyzed in self-grafted pepper plants (variety onto variety, V/V) and variety grafted onto NIBER® (V/N) at 4, 24, and 48h after severe water stress was induced by PEG addition. After 48h, WUE in V/N was higher than in V/V, due to major stomata closure to maintain water retention in the leaves. This can be explained by the higher abscisic acid (ABA) levels observed in the leaves of V/N plants. Despite the interaction between ABA and the ethylene precursor, 1-aminocyclopropane-1-carboxylic acid (ACC), in relation to stomata closure is controversial, we observed an important increase of ACC at the end of the experiment in V/N plants coinciding with an important rise of the WUE and ABA. The maximum concentration of jasmonic acid and salicylic acid after 48h was found in the leaves of V/N, associated with their role in abiotic stress signaling and tolerance. Respect to auxins and cytokinins, the highest concentrations were linked to water stress and NIBER®, but this effect did not occur for gibberellins. These results show that hormone balance was affected by water stress and rootstock genotype, where NIBER® rootstock displayed a better ability to overcome short-term water stress.